Low-frequency magnetic sensing by magnetoelectric metglas/bidomain LiNbO3 long bars - Turutin, Andrei V. (2018)
We present an investigation into the magnetic sensing performance of magnetoelectric bilayered metglas / bidomain LiNbO3 long thin bars operating in a cantilever or free vibrating regime and under quasi-static and low-frequency resonant conditions. Bidomain single crystals of Y+128o-cut LiNbO3 were engineered by an improved diffusion annealing technique with a polarization macrodomain structure of the “head-to-head” and “tail-to-tail” type. Long composite bars with lengths of 30, 40 and 45 mm, as well as with and without attached small tip proof masses, were studied. ME coefficients as large as 550 V/cm∙Oe, corresponding to a conversion ratio of 27.5 V/Oe, were obtained under resonance conditions at frequencies of the order of 100 Hz in magnetic bias fields as low as 2 Oe. Equivalent magnetic noise spectral densities down to 120 pT/Hz1/2 at 10 Hz and to 68 pT/Hz1/2 at a resonance frequency as low as 81 Hz were obtained for the 45 mm long cantilever bar with a tip proof mass of 1.2 g. In the same composite without any added mass the magnetic noise was shown to be as low as 37 pT/Hz1/2 at a resonance frequency of 244 Hz and 1.2 pT/Hz1/2 at 1335 Hz in a fixed cantilever and free vibrating regimes, respectively. A simple unidimensional dynamic model predicted the possibility to drop the low-frequency magnetic noise by more than one order of magnitude in case all the extrinsic noise sources are suppressed, especially those related to external vibrations, and the thickness ratio of the magnetic-to-piezoelectric phases is optimized. Thus, we have shown that such systems might find use in simple and sensitive room-temperature low-frequency magnetic sensors, e.g., for biomedical applications.